Microbial Consortium for Processing Secondary Collagen-Containing Raw Materials into Feeds for Farm Animals - M. Dragunova, M.; V. Pozdnyakova, A.; K. Asyakina, L.; V. Kriger, O.; S. Velichkovitch, N.; V. Kozlova, O.; S. Milentieva, I.; Y. Prosekov, A. (International Journal of Engineering and Technology, 2018)
In recent years, the problem of processing and rational use of the secondary raw materials of the meat industry is becoming relevant all over the world. Pork skin or wastes accumulate in significant quantities at meat-packing plants and slaughter houses in livestock farms. There are various technologies for processing collagen-containing raw materials, but their widespread introduction to enterprises is constrained by high cost. One of the effective approaches to solving this problem is the processing of collagen-containing wastes of pig complexes by biotechnological methods. For these purposes, compositions of consortia based on yeast have collagenase activity: Clavispora lusitaniae Y-3723, Candida utilis Y-263, Candida lipotica Y-3153, Candida lipotica Y-3157, Candida arthrobotrys F-1138. The compositions of nutrient media for co-cultivation of yeast were selected: temperature, pH, duration of cultivation. It was found that the degree of biodegradation of collagen-containing raw materials under the action of the consortia is 89.7%. The mass fraction of protein in the hydrolysates of collagen-containing raw materials is 78.15%, which opens prospects for their use as feed for farm animals.Â Â